Scientific quality of original research articles on environmental tobacco smoke - Barnes, D. E. (BMJ Group, 1997)
OBJECTIVE: To evaluate the scientific quality of original research articles on the health effects of environmental tobacco smoke; to determine whether poor article quality is associated with publication in non-peer-reviewed symposium proceedings or with other article characteristics. DESIGN: Cross sectional study of original research articles on the health effects of environmental tobacco smoke published in peer reviewed journals and non-peer-reviewed symposium proceedings from 1980 to 1994. Article quality was assessed by two independent reviewers who used a valid and reliable instrument, were unaware of study hypotheses, were blinded to identifying characteristics of articles, and had no disclosed conflicts of interest. PARTICIPANTS: All symposium articles (n = 68) and a random sample of peer reviewed journal articles (n = 68) that satisfied inclusion/exclusion criteria. MAIN OUTCOME MEASURE: Mean quality scores, which could range from 0 (lowest quality) to 1 (highest quality). RESULTS: Using multivariate regression analysis, symposium articles were of poorer scientific quality than peer reviewed journal articles when controlling simultaneously for the effects of study design, article conclusion, article topic, and source of funding acknowledged (P = 0.027). Article quality was not associated with either source of funding acknowledged or article conclusion in multivariate analyses. CONCLUSIONS: In published reports on environmental tobacco smoke, non-peer-reviewed symposium articles tend to be of poor quality. These articles should not be used in scientific, legal, or policy settings unless their quality has been independently assessed.